2006
DOI: 10.1892/0891-6640(2006)20[1018:hatlsa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia and Tumor Lysis Syndrome Associated with peritoneal Mesothelioma in a Horse

Abstract: A n 11-year-old Lipizzaner mare was referred for lethargy, abdominal distention, coughing, and weakness of 1 month's duration. The mare had been regularly dewormed and vaccinated against tetanus, influenza, and Eastern and Western equine encephalitis. Serum agar gel immunodiffusion assay for equine infectious anemia was negative.The mare was weak, lethargic, and mildly dehydrated. Abdominal distention was prominent (Fig 1), and borborygmi were absent. Mucous membranes were pale with a capillary refill time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
(2 reference statements)
0
10
0
Order By: Relevance
“…Seizures and cardiac arrhythmias associated with ATLS are usually attributed to metabolic changes, including hyperkalemia, hyperphosphatemia, and hypocalcemia (Davidson et al 2004). Similar metabolic derangements have been described in cats, dogs, and a horse with ATLS (Calia et al 1996;LaCarrubba et al 2006;Laing and Carter 1988;Mylonakis et al 2007;Vickery and Thamm 2007), but histopathology has not been routinely reported. A single series of three canine ATLS cases revealed generalized microthrombi in the necropsy specimens of two dogs (Laing and Carter 1988).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Seizures and cardiac arrhythmias associated with ATLS are usually attributed to metabolic changes, including hyperkalemia, hyperphosphatemia, and hypocalcemia (Davidson et al 2004). Similar metabolic derangements have been described in cats, dogs, and a horse with ATLS (Calia et al 1996;LaCarrubba et al 2006;Laing and Carter 1988;Mylonakis et al 2007;Vickery and Thamm 2007), but histopathology has not been routinely reported. A single series of three canine ATLS cases revealed generalized microthrombi in the necropsy specimens of two dogs (Laing and Carter 1988).…”
Section: Introductionmentioning
confidence: 95%
“…Clinically significant ATLS, with end-organ compromise, occurs in approximately 5% of all patients with hematologic malignancies (Hochberg and Cairo 2008) and in up to 25% of highrisk patients, including those with T-cell acute lymphoblastic leukemia and Burkitt's lymphoma (Coiffier et al 2008). Acute tumor lysis syndrome also develops secondary to hematopoietic malignancies and solid tumors in veterinary species (LaCarrubba et al 2006;Radaelli et al 2009), although the overall incidence is unknown. Life-threatening complications of ATLS include acute renal failure, cardiac arrhythmias, neurologic perturbations, and metabolic acidosis (Davidson et al 2004;Hochberg and Cairo 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Blood cultivation was not done in this mare. The other possibility is tumor lysis syndrome (TLS), which was described in a horse with peritoneal mesothelioma (LaCarrubba et al, 2006). TLS is a well recognized oncologic emergency in humans characterized by severe metabolic derangements such as acute renal failure, hyperkalemia, hyperphosphatemia, hypokalcemia.…”
Section: Discussionmentioning
confidence: 99%
“…Neoplastic transformation of these cells is an infrequent occurrence in domestic animals. 3,8 There have been a small number of reports of mesothelioma in horses, including tumors arising within the pleural cavity, 6,7 peritoneal cavity, 4,10 and pericardium, 12 and those that had spread to involve more than one of these sites. 6,13,14 The ages of the horses ranged from 2 to 27 years.…”
mentioning
confidence: 99%
“…The clinical presentation depended on the site affected; for example, tumors arising in the peritoneal cavity typically produced marked abdominal distension due to ascites, as in other species. 4,8,10 Mesotheliomas have been classified into 3 main histological types: epithelioid, biphasic, and sarcomatoid. 8 Additional epithelioid variants include tubopapillary, acinar, polygonal, microcystic, clear cell, deciduoid, desmoplastic, and lymphohistiocytic mesotheliomas.…”
mentioning
confidence: 99%